How to increase the performance in Special Olimpics (SO) table tennis players - Inbal, Bechar; Grosu, Emilia Florina; Teodor Grosu, Vlad (Arena-Journal of Physical Activities, 2017)
Purpose of Study: the present study sought to discover the ways and extent by which a special training program affects the improvement of table tennis skills of SO (Special Olympics) participants. The aims of this study was: Â 1. to develop an integrative Physical activity program for athletes who partici- pate in table tennis games in SO; 2. To explore the influence of an applicable training program on the balance, hand-eye coordination, power regulation and Movement integration among athletes who participate in table tennis games in SO; 3. To develop skills tests for intellectually disabled athletes who participate in table tennis games in SO, in four aspects: balance, eye- hand coordination, power regulation and coordination.Methods and Research tools: The samples of subjects tested are aged 30Â±5 and 32Â±5, 10 participants in experimental group and 10 participants in con- trol group. 4 Skills tests administered before and after the training program. Findings and Results was performed using SPSS 15.0. For the comparison of means between groups of subjects we applied Cronbachâ€™s Alpha. Partici- pating in training improved significantly in all four skills tested: balance, hand-eye coordination, power regulation of power and coordination. Com- pared to the control group which did not show any change in the motor skills of the participants. In the beginning parents did not believe in the traineeâ€™s ability to change and improve, but at the end they made a significant change in perception and the ability to recognize their variability.Conclusions and Recommendations: the conclusion describes a conceptual TTSOT model that combines different disciplines, all of which together make up the training program success. The model represents six different aspects of the same model application components: an aspect of learning (trainee), an aspect of teaching trainer ) socio-motivational aspects, ecological aspects, and cognitive- emotional aspects.The practical implications make practical conclusions concept of training Special Olympics athletes participating in table tennis. Â Implementation of the model can be expressed in curriculum in schools for special education and in vocational training for Special Olympics Games in the table tennis domain in particular and other sports field including these skills in gen- eral.